Clinical and tomographic stability in young patients with keratoconus or suspicious tomographies for keratoconus (2020)
ABSTRAC: Purpose: To evaluate tomographic variables related to ectasia progression in patients < 18 years with keratoconus (KC) or suspicious tomographies for keratoconus (STK) from a private clinic in Medellin, Colombia, to determine the need for crosslinking in a pediatric population. Design: Mixed prospective-retrospective descriptive study. Participants: Patients were evaluated from 2012 to 2020. All patients had a tomography by rotating Scheimpflug (Pentacam; Oculus Gmbh, Wetzlar, Germany), with a BAD-D ≥ 1.6 in the included eye(s) on the Belin-Ambrósio display and a minimal repeat image at one year. 43 eyes of 24 patients with a follow up ranging from 1 to 8 years were included. Methods, Intervention, or Testing: All potential study subjects were reviewed by two independent cornea specialists with extensive knowledge in corneal imaging. Maps were graded as KC, STK or normal. Only patients where there was an agreement were included. Eye rubbing control was the mainstay of therapy with topical antiallergics, anti-inflammatories and an allergist consult if needed. Crosslinking (CXL) was performed only if progression was documented. The definition of progression from 2012 to 2017 required a significant variation in two of four parameters: anterior best fit sphere (BFS), posterior BFS, minimum corneal thickness or an increase in the Kmax (maximum keratometry) values. After June 2017 the Belin ABCD progression parameters were utilized; crossing beyond the solid red line (95% confidence interval for patients with keratoconus) of either the anterior radius of curvature (A), the posterior radius of curvature (B) or the minimum corneal thickness (C) on at least two consecutive occasions was considered progression. Main Outcome Measures: Percentage of progression as defined above in KC or TSK eyes, number of lines gained or lost of DCVA in all patients, CXL or not, and the variability of the A, B and C values of the ABCD display was calculated in stable, non-progressing TSK eyes. Results: 4 out of 12 eyes with KC (33,33%) and 1 of the 31 eyes with TSK (3.2%) met the criteria for progression and were and were CXL. No patient in either group lost DCVA with an average follow-up of 4,01 years (±1,78) (range 1,66-6,83) in KC group and of 3,47 years (±1,89) (Range 1,08-8) in TSK group. Conclusions: Strict control of eye rubbing combined with careful follow-up of children with tomographies suspiciuous of keratoconus or true keratoconus without undue loss of DCVA is successful to indicate CXL treatment and avoid vision loss